Species-site Suitability Assessment of Native Species in Pantabangan-Carranglan Watershed Using Geographic Information System (GIS) and Analytic Hierarchy Process (AHP). - Dolores, J. C.
Reforestation activities were employed in several locations of the Philippines due to deforestation. However, many of these efforts fail because of various reasons, one of which is the poor selection of species. This study aimed to improve chances of success of reforestation in one of the critical watersheds in the Philippines, the Pantabangan-Carranglan Watershed (PCW), through a Geographic Information System (GIS)-based species-site suitability assessment of selected native tree species. Thematic maps of soil properties, climate, topography, and biotic conditions were generated for the watershed. The silvical requirements of the selected native species were also established through a literature review. Thereafter, a species-site suitability analysis was done using a GIS platform with the importance of each site feature given different weights through an Analytic Hierarchy Process (AHP), an approach that hasn?t been done in previous GIS-based species-site suitability assessment. Results showed that of the three species analyzed, ?akle? [Albizia acle (Blanco) Merr.] was found to be the most suitable in the site, with 53% of the watershed falling under high suitability class, while ?dita? [Alstonia scholaris (L) R. Br.] and ?almaciga? [Agathis philippinensis (Warb.)] were both found to be suitable to the identified reforestation areas of PCW, signifying that they are able to potentially survive within the existing environmental conditions of the site. The generated spatial distribution maps of species-site suitability can serve as guides to the managers of the watershed in future reforestation activities.